EFFECT OF FERTILIZATION IN THE PRODUCTIVITY, QUALITY AND SANITY OF CULTIVATED POTATO IN THE MIDDLE-WEST OF PARANÁ - MALLMANN, Nicolau (Scientia Agraria, 2002)
The potato (Solanum tuberosum tuberosum L.) is an economically important crop for Brazil, particularly for the states of Paraná, Rio Grande do Sul, Minas Gerais, São Paulo and Santa Catarina, which are the main potato producers, corresponding to 95% of the 182,000 ha cultivated with potato in the whole country. This total potato cultivated area consists of three main cropping seasons: Raining, Drought and Winter. Although not standing high in the average yield, the State of Paraná ranks equal to Rio Grande do Sul in terms of cultivated area, which is one of the largest in Brazil: near 40,700 ha, as of 1999 data. In this context, the Central-West region of Paraná, where Guarapuava Fields (Campos de Guarapuava) area located has been striking for its outstanding potato tuber quality and yeld which are marketed as fresh, processed or as seed multiplication in its near 7,000 ha. Such high perfomance of Guarapuavas potato production is credited to an interaction of factors which can be identified as favorable climate and types, besides constant introduction of new cultivars, propagating material of known and certified origins, adequate planting seasons, integrated pest and disease management systems, appropriate fertilization and supplied irrigation, soil bed preparation, etc. Currently, however, the potato industry faces the challenge of an increasing production cost, environmental claims and potencial gains in yeld and quality. These factors require updated information which best support the decision makers toward promoting the potato crop. Among the most needed information stand those regarding soil and fertilization management. In this aspect, the fertilization applied to the potato crop has been basically and generally the 3 to 4 Mg.ha-1 of the formulation 40-140-80 and 40-160-80 (g.kg-1 of N-P2O5-K2O). Facing this reality, which disregard the variation factors, the present research was carried out. Thus, the aim of this work was to evaluate the potato response on the tuber production and quality over fertilization doses and application time parcels, as well as the general health of the cultivar Monalisa, which is one of that covers over ¾ of the potato areas. The treatments were doses and two application times of Nitrogen (Urea), Phosphorous (Supertriple) and doses and source of Potassium (KCl and K2SO4). The studies were conducted in the rain season of 1998/1999 (November through February), with experiments installed in a very acidic brown oxisol (Latossolo Bruno distrófico) type of soil, which is representative for the potato cropping region. The experimental design was 18 treatments with four replicates, totaling 72 blocks of 15m2, each composed of 5m long rows, planted with 14 tubers, spacing 0.75m from each other. The results showed an equivalent yeld and quality with reduced doses of P2O5 as compared to those usually applied by the potato producers. Timing for Nitrogen application favored some of the evalueted parameters. Increasing doses of K2O and origin os sulfur responded with improvement on either tuber yeld as well as quality. High K dosage lead to high yield and reduction of scab symptoms (Streptomyces scabies), black leg (Erwinia carotovora carotovora), late blight (Phytophthora infestans), dry rot (Fusarium solani) and early blight (Alternaria solani).